2010
DOI: 10.3109/00365548.2010.499541
|View full text |Cite
|
Sign up to set email alerts
|

Results of faecal donor instillation therapy for recurrent Clostridium difficile-associated diarrhoea

Abstract: We report a success rate of 83% with faecal donor instillation therapy (FDIT) in this retrospective study of 40 patients with recurrent Clostridium difficile-associated diarrhoea (CDAD), treated at a medium sized Norwegian hospital from 1994 through 2008. The stool transplant was instilled either in the duodenum through a gastroscope or in the colon through a colonoscope with next of kin or other household member as donor. In 29 cases (73%) the first treatment was successful, with no documented recurrence of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 18 publications
1
102
0
4
Order By: Relevance
“…There have been successful results, defined as clearance of diarrhea, or negative C. difficile toxin assays, with FMT administered to the proximal colon via colonoscope (see Table 1) [Arkkila et al 2010;Brandt et al 2012;Garborg et al 2010;Girotra et al 2011;Hamilton et al 2012;Hellemans et al 2009;Kelly et al 2012;Khoruts et al 2010;LundTonnesen et al 1998;Mattila et al 2011;Paterson et al 1994;Persky and Brandt, 2000;Rohlke et al 2010;Wettstein et al 2007;Yoon and Brandt, 2010], the distal lower GI tract via enema/rectal tube (see Table 2) [Borody et al 2001;Bowden et al 1981;Gustafsson et al 1999;Jorup-Ronstrom et al 2006;Kassam et al 2012;Louie, 2008;Paterson et al 1994;Schwan et al 1983;Silverman et al 2010;Tvede and Rask-Madsen, 1989;You et al 2008], and the upper GI tract via nasogastric (NG) tube/gastroscope (see Table 3) [Aas et al 2003;Duplessis et al 2011;Lund-Tonnesen et al 1998;MacConnachie et al 2009;Nieuwdorp et al 2008;Rubin et al 2009;Russell et al 2010].…”
Section: Fmt Methodologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…There have been successful results, defined as clearance of diarrhea, or negative C. difficile toxin assays, with FMT administered to the proximal colon via colonoscope (see Table 1) [Arkkila et al 2010;Brandt et al 2012;Garborg et al 2010;Girotra et al 2011;Hamilton et al 2012;Hellemans et al 2009;Kelly et al 2012;Khoruts et al 2010;LundTonnesen et al 1998;Mattila et al 2011;Paterson et al 1994;Persky and Brandt, 2000;Rohlke et al 2010;Wettstein et al 2007;Yoon and Brandt, 2010], the distal lower GI tract via enema/rectal tube (see Table 2) [Borody et al 2001;Bowden et al 1981;Gustafsson et al 1999;Jorup-Ronstrom et al 2006;Kassam et al 2012;Louie, 2008;Paterson et al 1994;Schwan et al 1983;Silverman et al 2010;Tvede and Rask-Madsen, 1989;You et al 2008], and the upper GI tract via nasogastric (NG) tube/gastroscope (see Table 3) [Aas et al 2003;Duplessis et al 2011;Lund-Tonnesen et al 1998;MacConnachie et al 2009;Nieuwdorp et al 2008;Rubin et al 2009;Russell et al 2010].…”
Section: Fmt Methodologiesmentioning
confidence: 99%
“…The choice of donors varies among studies, most frequently the donor has been an intimate partner, housemate, or family member [Borody et al 2004;Gough et al 2011;Rohlke et al 2010], however several studies used volunteer donors [Aas et al 2003;Borody et al 2004;Bowden et al 1981;Eiseman et al 1958;Garborg et al 2010;Hamilton et al 2012;Kassam et al 2012;Lund-Tonnesen et al 1998]. Lund-Tonnesen and colleagues used homologous feces from 1 healthy donor in 18 patients (17 colonoscope, 1 gastroscope) [LundTonnesen et al 1998].…”
Section: Donor Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Furthermore, the elderly are at increased risk for severe CD infections and morbidity and mortality related to CD. [6][7][8] Recurrent infections are concerning due to the risk of both adverse outcomes among individual patients with each subsequent occurrence and spread of CD to others due to incompletely eradicated infections. 9 Studies examining CD recurrence across all age groups have identified older age, severe CD infection, use of non-CD-related antibiotics, use of antacid medications, and hospital exposure as risk factors for CD recurrence.…”
Section: Introductionmentioning
confidence: 99%